2010
DOI: 10.1007/s00425-010-1147-4
|View full text |Cite
|
Sign up to set email alerts
|

A tomato bZIP transcription factor, SlAREB, is involved in water deficit and salt stress response

Abstract: Abiotic stresses such as cold, water deficit, and salt stresses severely reduce crop productivity. Tomato (Solanum lycopersicum) is an important economic crop; however, not much is known about its stress responses. To gain insight into stress-responsive gene regulation in tomato plants, we identified transcription factors from a tomato cDNA microarray. An ABA-responsive element binding protein (AREB) was identified and named SlAREB. In tomato protoplasts, SlAREB transiently transactivated luciferase reporter g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(118 citation statements)
references
References 62 publications
4
113
0
1
Order By: Relevance
“…These results suggested that this class of bZIPs plays a role in abiotic stress response in the Solanum genus. In another study, Hsieh et al (2010) observed that the overexpression of SlAREB is responsible for increasing tolerance to water and salinity in tomato plants. The sverproduction of SlAREB in transgenic tomato plants regulated genes AtRD29A, AtCOR47, and SlCI-like dehydrin under ABA and abiotic stress treatments.…”
Section: Applicable Tomato Transformationmentioning
confidence: 97%
“…These results suggested that this class of bZIPs plays a role in abiotic stress response in the Solanum genus. In another study, Hsieh et al (2010) observed that the overexpression of SlAREB is responsible for increasing tolerance to water and salinity in tomato plants. The sverproduction of SlAREB in transgenic tomato plants regulated genes AtRD29A, AtCOR47, and SlCI-like dehydrin under ABA and abiotic stress treatments.…”
Section: Applicable Tomato Transformationmentioning
confidence: 97%
“…In addition, the homozygous T-DNA insertional mutants Osabf-1 and Osabf-2 were more sensitive to drought and salt stress than WT plants (Hossain et al 2010). Constitutive expression of the AREB ortholog TF from tomato (Solanum lycopersicum), SlAREB, increased tolerance to water deficit and high salinity in Arabidopsis and tomato plants, maintaining photosystem II and membrane integrities, and water content (Hsieh et al 2010).…”
Section: Regulation Of the Responsesmentioning
confidence: 99%
“…A number of studies have evaluated the function of group A TFs in rice, their results demonstrating that the overexpression of OsABI5 lead to a higher sensitivity to salt stress (Zou et al, 2008), and that of OsABF1 and OsABF2 enhanced the abiotic stress signaling (Hossain et al, 2010a,b). In Arabidopsis, the roles of AREB1 and AREB2 in response to ABA, drought, and high salt stresses have been well-examined (Hsieh et al, 2010). Although several reports on bZIP family TFs in Arabidopsis and rice are available, similar studies in carrot are lacking.…”
Section: Introductionmentioning
confidence: 99%